Nonlinear Dynamics of Chaotic and Stochastic Systems Tutorial and Modern Developments - Anishchenko, Vadim S.; Astakhov, Vladimir; Vadivasova, Tatjana; Neiman, Alexander; Schimansky-Geier, Lutz.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This book is a complete treatise on the theory of nonlinear dynamics of chaotic and stochastic systems. It contains both an exhaustive introduction to the subject as well as a detailed discussion of fundamental problems and research results in a field to which the authors have made important contributions themselves. Despite the unified presentation of the subject, care has been taken to present the material in largely self-contained chapters. The present book can thus be used either as a textbook by graduate students or as a modern monograph by researchers in this field. The second edition has been substantially enlarged to include sections on statistical properties of dynamical chaos, on effects of synchronization in oscillatory systems and on synchronization in living systems.
Tutorial -- Dynamical Systems -- Fluctuations in Dynamical Systems -- Synchronization of Periodic Systems -- Dynamical Chaos -- Routes to Chaos -- Statistical Properties of Dynamical Chaos -- Synchronization of Chaos -- Effects of Synchronization in Extended Self-Sustained Oscillatory Systems -- Synchronization in Living Systems -- Controlling Chaos -- Reconstruction of Dynamical Systems -- Stochastic Dynamics -- Stochastic Resonance -- Synchronization of Stochastic Systems -- The Beneficial Role of Noise in Excitable Systems -- Noise Induced Transport.
Keywords: Physics; Applied mathematics; Engineering mathematics; Probabilities; Statistical physics; Dynamical systems; Vibration; Dynamics; Physics; Statistical Physics, Dynamical Systems and Complexity; Mathematical Methods in Physics; Probability Theory and Stochastic Processes; Applications of Mathematics; Vibration, Dynamical Systems, Control; Electronic books